1999
DOI: 10.1002/(sici)1522-2594(199904)41:4<686::aid-mrm6>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in myocardial oxygenation and perfusion under pharmacological stress with dipyridamole: Assessment usingT*2 andT1 measurements

Abstract: The aim of this pilot‐study was to evaluate changes in myocardial oxygenation and perfusion under pharmacological stress with dipyridamole (DIP) by means of MRI. Twenty healthy volunteers were examined using a multi‐echo gradient‐echo sequence. The differential myocardial signal response due to the blood oxygen level dependent (BOLD) effect was studied under variable conditions of myocardial oxygen supply caused by the vasodilator DIP. Unlike contrast agents (CA) methods, which require at least two injections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…T 2 * mapping was more sensitive to oxygenation changes but showed more variability. The fact that BOLD CMR shows a linear correlation to coronary sinus oxygen saturation is in agreement with the expected proportionality between the BOLD effect and the absolute tissue content of deoxygenated hemoglobin[13,19,20]. Importantly, a previous theoretical study by Dharmakumar et al demonstrated that the BOLD signal is blood volume-independent[21].…”
Section: Discussionsupporting
confidence: 78%
“…T 2 * mapping was more sensitive to oxygenation changes but showed more variability. The fact that BOLD CMR shows a linear correlation to coronary sinus oxygen saturation is in agreement with the expected proportionality between the BOLD effect and the absolute tissue content of deoxygenated hemoglobin[13,19,20]. Importantly, a previous theoretical study by Dharmakumar et al demonstrated that the BOLD signal is blood volume-independent[21].…”
Section: Discussionsupporting
confidence: 78%
“…23,24 Previously, both skeletal and cardiac muscle have demonstrated increased intracellular edema related to inflammatory cytokines associated with cancer before treatment. 25 Thus, our observation of T1-related changes in newly diagnosed cancer patients may be related to the presence of comorbidities, cancer-related processes, or a mixture of both.…”
Section: Discussionmentioning
confidence: 99%
“…For T2*, susceptibility artefacts are often seen at the myocardial-lung interface, in the inferior wall due to heavy iron loading in the liver, as a result of cardiac motion, and from veins in the atrioventricular groove containing deoxygenated blood. Although blood oxygenation level affects T2* in vivo, T1 and T2 are less affected and in any case, this is unlikely to affect post-mortem T1 or T2 values [36]. …”
Section: Discussionmentioning
confidence: 99%